Persepsi Nilai Mampu Memediasi Terwujudnya Kepuasan Pelanggan - Riki Siril Wafa; Sujito Sujito; DC Kuswardani (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This Research Is To Examine And Analyze The Effect Of Customer Experience, Customer Expectations And Perceived Quality On Customer Satisfaction With Perceived Value As An Intervening Variable In An Empirical Study On Zeta Green At Pt Dipo Technology. The Problem Faced By Pt Dipo Technology Is An Increase In Complaints From Customers And A Decreased Percentage Of Satisfaction. This Research Was Conducted Using The Quantitative Research Method And Analyzed Using Smartpls 4. The Population In This Study Were Customers Who Had Purchased Zeta Green Products More Than Once, A Total Of 171 People. The Sample Used Was 120 People. The Determination Of The Sample In This Study Used Non-Probability Sampling And The Sampling Technique Was Purposive Sampling. The Results Of The Analysis Show That Customer Experience, Customer Expectations And Perceived Quality Have A Positive And Significant Effect On Perceived Value And Customer Satisfaction. Perceived Value Is Able To Mediate The Effect Of Customer Experience, Customer Expectations And Perceived Quality On Customer Satisfaction. Based On The Adjusted R Square Value, It Explains That Customer Experience, Customer Expectations, Perceived Quality And Perceived Value Affect Customer Satisfaction By 81.3% And The Rest Is Explained By Other Variables Not Present In The Study.